CARTILLAGE MICROCRYSTALLIZATION PHENOMENON IN COXARTHROSIS AND AVASCULAR NECROSIS OF FEMORAL HEAD - A I Dubikov; Maksim Alexandrovich Kabalyk; T Yu Petrikeeva; I I Kuzmin; A A Korabtsov (Научно-практическая ревматология, 2012)
Osteoarthritis (OA) is the most prevalent pathology in routine rheumatologic practice. The concept of calcium-containing crystals deposition within articular cartilage and paraarticular tissues remains the centerpiece among existing theories on the pathogenesis of OA. Objective — radiographic structural analysis of articular cartilage microcrystallization phenomenon in patients with OA and avascular necrosis of femoral head (ANFH). Material and methods. Overall 80 patients after total hip replacement procedure due to coxarthrosis or ANFH were enrolled into this study. The control group included 20 patients with total hip arthroplasty for femoral neck fractures. X-ray diffractometer and scanning electron microscope were used to detect crystal deposition. Results. Cartilage mineralization was observed in 92% of patients with advanced OA and in 100% of ANFH patients. The analysis revealed predominance of calcium phosphate monobasic crystals. X-ray diffraction can be used for practical and investigational purposes.